2014
DOI: 10.1159/000358014
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Deep Brain Stimulation Electrode Impedance over Years Following Electrode Implantation

Abstract: Background: Deep brain stimulation (DBS) electrode impedance is a major determinant of current delivery to target tissues, but long-term variation in impedance has received little attention. Objectives: To assess the relationship between electrode impedance and time in a large DBS patient population and characterize the relationship between contact activity and impedance. Methods: We collected retrospective impedance and programming data from 128 electrodes in 84 patients with Parkinson's disease, essential tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 38 publications
5
88
1
Order By: Relevance
“…As in past studies,21 22 impedance was found to vary by contact position along the DBS electrode, with mean impedance highest in contact 0 and lowest in contact 2, at baseline (ie, during initial programming, typically 3 weeks following electrode implantation) and over time. Impedance has also been found to decrease over time and with contact activity21 22; this result was verified in the present study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…As in past studies,21 22 impedance was found to vary by contact position along the DBS electrode, with mean impedance highest in contact 0 and lowest in contact 2, at baseline (ie, during initial programming, typically 3 weeks following electrode implantation) and over time. Impedance has also been found to decrease over time and with contact activity21 22; this result was verified in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Quadripolar DBS electrode contacts are numbered 0–3, from caudal to rostral-most. Two studies of impedance over time since implantation found that impedance was highest in contact 0 and lowest in contact 2 21 22. Assuming relatively consistent electrode placement with respect to STN, contact number is likely to correlate with anatomic location.…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications have reported transient increases in impedance in depth and subdural electrodes followed by a decrease after the acute phase of the tissue reaction has passed in animals and in a large clinical trial [1,6,10,12,16,17]. We have previously reported "… a trend for impedance to increase over the first 12 weeks after implant.…”
Section: Discussionmentioning
confidence: 70%
“…Our study was designed to address the unresolved question of whether the modality of delivery of electrical charge in any way alters the clinical benefit or side effects of stimulation. To control for impedance changes, this study was conducted 2 years after surgery, when the chronic impedance values are thought to be established [14,15]. Thus, the clinical effects of differing stimulus waveform could be studied in isolation.…”
Section: Introductionmentioning
confidence: 99%